1998
DOI: 10.1080/01971529808005468
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an ELISA to Measure Antibody Responses to Both the Nucleocapsid and Spike Proteins of Canine Coronavirus

Abstract: A rapid and reproducible enzyme linked immunosorbent assay (ELISA) was developed for detection of canine coronavirus (CCV) specific antibodies directed to both the nucleocapsid (NC) and the spike (S) proteins. The coating antigen, a methanol-treated, S-protein enriched preparation, was produced by subjecting infected cells to Triton X-114 detergent followed by phase separation. The sensitivity of this assay was determined by following the course of infection in dogs experimentally infected with CCV. The specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The diagnostic methods presented so far have been direct diagnostic methods, while serology offers an alternative, indirect approach to pathogen detection. Serology, screening for the presence of specific antibodies in the serum of animals, can be a useful indicator of previous exposure to a pathogen, especially for viruses, and this type of screening is used routinely in clinical and veterinary medicine (Palmer‐Densmore, Johnson & Samara 1998; Yüce, Yücesoy, Genç, Sayan & Uçan 2001; Fournier & Raoult 2003).…”
Section: New Molecular Methods With Potential For Use In Aquaculturementioning
confidence: 99%
“…The diagnostic methods presented so far have been direct diagnostic methods, while serology offers an alternative, indirect approach to pathogen detection. Serology, screening for the presence of specific antibodies in the serum of animals, can be a useful indicator of previous exposure to a pathogen, especially for viruses, and this type of screening is used routinely in clinical and veterinary medicine (Palmer‐Densmore, Johnson & Samara 1998; Yüce, Yücesoy, Genç, Sayan & Uçan 2001; Fournier & Raoult 2003).…”
Section: New Molecular Methods With Potential For Use In Aquaculturementioning
confidence: 99%
“…The neutralizing test (NT) (Mochizuki et al, 1987;Appel, 1988) and the enzymelinked immunosorbent assay (ELISA) (Rimmelzwaan et al, 1991;Tuchiya et al, 1991;Palmer-Densmore et al, 1998) have been reported as antibody tests against CCV. NT is superior in speci¢city, but it is not appropriate for rapid diagnosis, since it requires several days to obtain a result.…”
Section: Introductionmentioning
confidence: 99%